Perceived Benefits and Pre-Design Environmental Impact Assessment of Eco-Friendly Ornament Development - Swapnil Singh,; Poonam Singh,; Preeti Singh,; Amrit Warshini, (Indian Journal of Extension Education, 2025)
The study examined the environmental benefits and pre-design impact assessments of eco-friendly ornaments in rural Uttar Pradesh, focusing on Ayodhya district. A sample of 240 respondents was selected from 24 villages using a multistage random sampling method. Data were collected through structured interviews, surveys, and direct observations, and analyzed using descriptive statistics, chi-square tests, and Student’s t-test. The results, conducted in 2024-2025, show that 58.75% of respondents supported eco-friendly ornaments to promote environmental safety (χ² = 191.95, p < 0.05). However, when it came to integrating environmental considerations during the design phase, durability (35.41%) was the most frequently cited factor; however, the differences were not statistically significant (t = 0.167, p < 0.182). In terms of ecological benefits, energy saving (40.41%) and fossil fuel alternatives (30.41%) were the most recognized advantages, with statistical significance (χ² = 48.61, p < 0.05). These findings highlight a strong environmental motivation among consumers in rural areas, although sustainability is not fully integrated into the early stages of product design. The study emphasizes the need for interventions that raise awareness and build capacity to ensure that sustainability becomes a key consideration in the design process, ultimately promoting more environmentally responsible ornamentation practices in rural India.